3D kinematic in freestyle cross country skiing technique during World Championships in Val di Fiemme 2013 - Canclini, A.; Canclini, A. G.; Baroni, G.; Pozzo, R. (Sciene and nordic skiing III, 2016)
The "new" freestyle (FT) in XCS was formally introduced in 1985 in specialized races in addition to the original races in classical technique. In the last three decades the freestyle has considerably developed due to the new equipment and materials, better ski tracks preparation, renovation in the training methodology and in the enhanced skiers techniques depending in terrain and/or drag forces. A Free skiing race challenges the athletes to master a wide range of speeds and slopes and to adapt their technique accordingly. Thus, skiers possess different skiing techniques and continuously change between them during a race. The skating technique has five predominant subtechniques, known as gears (G1-5) as suggested by Nilsson et al. (2004), where G2, G3 and G4 replace the old names V1-V2 and V2altemate. In the `90s several studies have been conducted in attempt to describe the most relevant aspects of XCS freestyle, but the kinematic information is generally limited in the velocity range. More recently Kvamme (2005), Stöggl (2010), Andersson (2010) compared biomechanical characteristics of the main skating techniques. In the previous studies (Canclini 2013) we considered the G3 and G4 gears used in easy terrain at high velocities or in snow conditions with low friction. The lower gear G2, used on uphill, is an asymmetrical technique involving one poling action over every second leg stroke. The aim of this work was to collect and to analyze the 3D kinematics of the typical stride G2 in Free style XCS performed by elite skiers engaged in recent World Championships race. (Original introduction)